The Training Component in Tropical Agriculture: A Management Perspective - James W. King (Journal of Applied Communications, 1986)
By the year 2000 a world population of more than 6 billion will require an agricultural output some 50 to 60 percent greater than in 1980. Demand for food and agricultural products in developing countries will double. It is essential, within the next few years, to make many of the decisions that will determine the world food situation in 1990, or even 2000. (FAO. 1980)